2017
DOI: 10.1001/jamaoncol.2016.3288
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Stratification by Combining BRAF V600E and TERT Promoter Mutations in Papillary Thyroid Cancer

Abstract: These results demonstrate a simple 4-genotype classification of PTC, particularly CPTC, with a disease-specific mortality risk order of the genetic duet>>>>BRAF V600E alone = TERT promoter mutation alone > wild-type for both genes, representing a powerful molecular prognostic system that can help pinpoint patients with the highest mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
210
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(226 citation statements)
references
References 37 publications
12
210
1
3
Order By: Relevance
“…33,34 Moreover, TERT promoter mutation alone has limited or virtually no effect on PTC-specific mortality. 35,36 Therefore, lack of information on TERT promoter mutation should not affect the clinical implications of this study on the use of BRAF V600E status in differentiating patient age-related mortality risk in PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Moreover, TERT promoter mutation alone has limited or virtually no effect on PTC-specific mortality. 35,36 Therefore, lack of information on TERT promoter mutation should not affect the clinical implications of this study on the use of BRAF V600E status in differentiating patient age-related mortality risk in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Another potential and more likely mechanism is the coexistence of BRAF V600E and TERT promoter mutations, which are synergistically associated with poor clinical outcomes in PTC, including disease recurrence and patient mortality. 35,36 Both BRAF V600E 20-22 and TERT promoter mutations 34 occur in PTC more commonly in older patients. The present results are also consistent with a previous finding that BRAF V600E and older patient age had a synergistic effect on PTC-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, alterations in the telomere 3D profile have been reported in a murine model of thyroid tumors [41]. Recurrent somatic mutations in the promoter of TERT, the catalytic subunit of the enzyme telomerase, has been reported in PTC [42], often in concomitance with mutated BRAF [43]. A subclonal distribution in the rare PTC that harbor the alteration, in contrast to a clonal distribution in the poorly-differentiated and anaplastic tumors has been observed [44].…”
Section: Discussionmentioning
confidence: 99%
“…Some groups report that co-occurrence of TERT promoter and BRAF mutations are associated with worse prognosis factors in thyroid cancer (Allory et al 2014, 2016a, Song et al 2016, whereas other authors have not found this association in other series (Melo et al 2014, George et al 2015, Nasirden et al 2016.…”
Section: Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 94%